Tracer Study of Graduates of PJKR UNNES on Teacher Competence in the Field of Physical Education - Pramono, Harry; Kusuma, Donny Wira Yudha; Hartono, Mugiyo; Annas, Mohammad; S, Adi; Wijayanti, Dwi Gansar Santi (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2023)
Alumni is a means of promotion and curriculum development of a study program. Based on this background problem, this research focuses on finding data on graduates or alumni through tracer studies. The research design uses qualitative research. The population in this study were all graduates of the Department of Physical Education, Health and Recreation (PJKR) Semarang State University. The data collection method used by researchers is: a graduate tracer study system is carried out online through the development of an "alumni portal" which contains alumni respirators and databases that can be accessed online. The analytical method used to analyze the data obtained in this study are as follows: (a) Univariate analysis or single frequency analysis is intended to analyze only one variable that you want to know, for example the waiting period for graduates to get a job (b) bivariate analysis is intended to provide an explanation regarding the relationship between one variable and another, for example the suitability between lecture material and competency in employment, and (c) multivariate analysis is used to determine various variables, from the simplest to the most complex.